solution-1759325
solution-1759325
solution-1759325
REVISION TEST 6
Class 12 - Mathematics
Section A
1. (a)
Det (A)
Explanation:
|B-1AB| = |B-1| × |A| × |B|
1
× |A| × |B| = |A|
B
2. (a) 9
Explanation:
IAA'| = |A| |A'| = (-3)(-3) = 9
3. (a) 16
Explanation:
Since, A is a square matrix of order 3 i.e. n = 3
we know that
|adj A| = (A)n-1
2
=2 (3−1)
...(∵ |A| = 2)
= 24
= 16
d −b
4. (a) [ ]
−c a
Explanation:
a b
S = [ ]
c d
M11 = d ⇒ A11 = d
M12 =c ⇒ A12 = -c
M21 =b ⇒ A21 = -b
M22 =a ⇒ A22 = a
d −b
⇒Ad(A) = [ ]
−c a
5.
(c) ±2
Explanation:
Since, the area of the △ABD is 3 sq units, then we have
∣1 3 1∣
1 ∣ ∣
0 0 1 = ±3
2 ∣ ∣
∣k 0 1∣
1
⇒ [0 + 0 − 1(0 − 3k)] = ±3
2
3k
⇒ = ±3
2
⇒ k = ±2
6.
(d) 0
Explanation:
0
1/5
7.
(c) 6
Explanation:
∣0 2 0 ∣
∣ ∣
λ 3 λ = - 16 then the sum of two values of λ is
∣ ∣
∣λ 5 6 ∣
∣0 2 0 ∣
∣ ∣
∣
λ 3 λ
∣
= -16 ⇒ - λ (12 - 0) + λ (2λ - 0) = -16
∣λ 5 6 ∣
8.
(d) infinitely many solutions
Explanation:
x + 2y = 5,
4x + 8y = 20
1 2 x 5
⇒ A=[ , X =[
] ,B=[
] ]
4 8 y 20
|A| = 8 -8 = 0
8 −2
adjA = [ ]
−4 1
8 −2 5 40 − 40 0
now (adj A)B= [ ][ ]= [ ]= [ ] ⇒ (adj A)B = 0
−4 1 20 −20 + 20 0
9.
(b) adj A
Explanation:
adj A
10.
−1
(b) (A T
)
Explanation:
−1
T
(A )
11.
(d) singular
Explanation:
If A is singular matrix then adjoint of A is also singular.This is true becaue , if A is a singular matrix, Then det(A) = 0 ,and
hence the adjoint will also be zero.
12.
33
(d) 2
Explanation:
When a given matrix is singular then the given matrix determinant is 0.
|A| = 0
Given,
2/5
1 k 3
⎛ ⎞
A= ⎜3 k −2 ⎟
⎝ ⎠
2 3 −4
|A| = 0
1(-4k + 6) -k(-12 + 4) + 3(9 - 2k) = 0
-4k + 6 + 12k - 4k + 27 - 6k = 0
-2k + 33 = 0
k= .33
13.
(b) 2
Explanation:
|A| = 2, |adj A| = |A|2 - 1 = |A| = 2
14.
(d) |A| = 22|B|
Explanation:
2 2 1 1
Let A = [ ] and B = [ ]
4 0 2 0
Now, |A| = 0 - 8 = -8
and |B| = 0 - 2 = -2
Observe that |A| = 4(-2) = 22 |B|
15.
(c) |A|6
Explanation:
If A is a non singular matrix of order 3, then |adj(A3)| = (|A3|)2 = (|AAA|)2 = (|A| |A| |A|)2 = (|A|3)2 = |A|6 .
Section B
∣ x 2 ∣ ∣ 6 2∣
16. we have, ∣ ∣ = ∣ ∣
∣ 18 x∣ ∣ 18 2∣
⇒ x2 – 36 = 36 - 36
⇒ x2 = 36
2
⇒ x + 1 = 36 + 1 = 37
Section C
17. We have |A| = = 1 (16 – 9) –3 (4 – 3) + 3 (3 – 4) = 1 ≠ 0
Now A11 = 7, A12 = –1, A13 = –1, A21 = –3, A22 = 1, A23 = 0, A31 = –3, A32 = 0, A33 = 1
7 −3 −3
⎡ ⎤
Therefore adjA = ⎢ −1 1 0⎥
⎣ ⎦
−1 0 1
1 3 3 7 −3 −3
⎡ ⎤⎡ ⎤
Now A(adjA) = ⎢ 1 4 3 ⎥ ⎢ −1 1 0⎥
⎣ ⎦⎣ ⎦
1 3 4 −1 0 1
7 − 3 − 3 −3 + 3 + 0 −3 + 0 + 3
⎡ ⎤
= ⎢7 − 4 − 3 −3 + 4 + 0 −3 + 0 + 3 ⎥
⎣ ⎦
7 − 3 − 4 −3 + 3 + 0 −3 + 0 + 4
3/5
1 0 0 1 0 0
⎡ ⎤ ⎡ ⎤
= ⎢0 1 0 ⎥ = (1) ⎢0 1 0 ⎥ = |A| ⋅ 1
⎣ ⎦ ⎣ ⎦
0 0 1 0 0 1
7 −3 −3 7 −3 −3
⎡ ⎤ ⎡ ⎤
Also A −1
=
1
adjA =
1
1
⎢ −1 1 0 ⎥ = ⎢ −1 1 0⎥ .
|A|
⎣ ⎦ ⎣ ⎦
−1 0 1 −1 0 1
A = ⎢3 4 −5 ⎥ , X = ⎢ y ⎥ and B = ⎢ −5 ⎥
⎣ ⎦ ⎣ ⎦ ⎣ ⎦
2 −1 3 z 12
∣3 −5 ∣
3
A12 = (−1) ∣ ∣ = −1(9 + 10) = −19
∣2 3 ∣
∣3 4 ∣
4
A13 = (−1) ∣ ∣ = 1(−3 − 8) = −11
∣2 −1 ∣
∣ −1 2∣
3
A21 = (−1) ∣ ∣ = −1(−3 + 2) = 1
∣ −1 3∣
∣1 2∣
4
A22 = (−1) ∣ ∣ = 1(3 − 4) = −1
∣2 3∣
∣1 −1 ∣
5
A23 = (−1) ∣ ∣ = −1(−1 + 2) = −1
∣2 −1 ∣
∣ −1 2 ∣
4
A31 = (−1) ∣ ∣ = 1(5 − 8) = −3
∣ 4 −5 ∣
∣1 2 ∣
5
A32 = (−1) ∣ ∣ = −1(−5 − 6) = 11
∣3 −5 ∣
∣1 −1 ∣
6
A33 = (−1) ∣ ∣ = 1(4 + 3) = 7
∣3 4 ∣
T
A11 A12 A13
⎡ ⎤
= ⎢ 1 −1 −1 ⎥
⎣ ⎦
−3 11 7
7 1 −3
⎡ ⎤
= ⎢ −19 −1 11 ⎥
⎣ ⎦
−11 −1 7
adj(A)
and A −1
=
|A|
7 1 −3
⎡ ⎤
= 1
4
⎢ −19 −1 11 ⎥
⎣ ⎦
−11 −1 7
4/5
Therefore, from Eq. (i), we get,
X = A-1B
x 7 1 −3 7
⎡ ⎤ ⎡ ⎤⎡ ⎤
1
⇒ ⎢y ⎥ = ⎢ −19 −1 11 ⎥ ⎢ −5 ⎥
4
⎣ ⎦ ⎣ ⎦⎣ ⎦
z −11 −1 7 12
x 49 − 5 − 36 8 2
⎡ ⎤ ⎡ ⎤ ⎡ ⎤ ⎡ ⎤
1 1
⇒ ⎢y ⎥ = ⎢ −133 + 5 + 132 ⎥ = ⎢4 ⎥ = ⎢1⎥
4 4
⎣ ⎦ ⎣ ⎦ ⎣ ⎦ ⎣ ⎦
z −77 + 5 + 84 12 3
5/5